EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023358 ZenodoArchiveConcept: 7023357 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023358 10.53832/edtechhub.0110 2405685:FUBDMTM8
Keywords: _r:AddedByZotZen

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found